TanDEM-X DEM derived Elevation Changes of the Greenland Ice Sheet - Wohlfart, Christian; Wessel, Birgit; Huber, Martin; Leichtle, Tobias; Abdullahi, Sahra; Kerkhoff, Silke; Roth, Achim (IGARSS 2018 - 2018 IEEE International Geoscience and Remote Sensing Symposium, 2018)
This study demonstrates the potential of TanDEM-X SAR imagery to analyze glacial elevation changes across entire Greenland. TanDEM-X time series data between 2010 and 2017 allow for consistent and high-resolution delineation of DEM at unprecedented quality. The first analysis reveal major elevation changes at the outlet and peripheral glaciers up to 15 m per between 2010/11 and 2011/12. The presented analysis will be extended until 2016/17. Furthermore, corrections related to snow penetration has to be considered in the current TanDEM-X DEM products